A STUDY TO CORRELATE THE SERUM URIC ACID LEVELS WITH THE DURATION AND SEVERITY OF MIGRAINE - KHAMESRA, RENU; PANCHAL, AKSHAY (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of the study were to assess the serum levels of uric acid in patients of migraine and to correlate the levels of uric acid with duration and severity of migraine. Methods: This observational study was conducted in patients with complaint of headache, due to migraine who attended neurology and general medicine out patients department of tertiary care teaching hospital of Udaipur, Rajasthan. Uric acid levels were compared between both the genders with respect to age group, frequency of attack, and duration of migraine. Uric acid levels were also correlated with different parameters. Results: A total of 500 patients were evaluated during the study period of 2 years. Mean uric acid in male patients was 5.02±1.40 mg/dl, and in females it was 4.99±1.39 mg/dl. Uric acid levels in male and female patients were found non-significant across all age groups, with duration of migraine and frequency of migraine attack (p>0.05). There was a significant correlation between uric acid levels and migraine severity in present study (p˂0.05), but there was no correlation with age, duration of migraine, and frequency of migraine attacks per month (p>0.05). Conclusion: The study concluded that uric acid levels are within normal range in all age group as well as either of gender in patients of migraine. Hence, there is no relation between uric acid and duration and frequency of migraine but positive correlation with severity of migraine.